FDA's proposed rule and its regulatory impact on emerging and reemerging neglected tropical diseases in the United States. - Alberto E Paniz-Mondolfi; Juan David Ramírez (Public Library of Science (PLoS), 2024)
Diagnosing infectious diseases significantly influences patient care, aiding in outbreak identification, response, and public health monitoring. However, the range of FDA-approved molecular tests remains notably limited, especially concerning neglected tropical diseases (NTDs). Drawing upon our experience as one of the largest healthcare networks in the greater New York metropolitan area, this viewpoint manuscript aims to spotlight the existing diagnostic landscape and unmet clinical needs for 4 emerging NTDs increasingly prevalent in the United States, additionally, it delves into the possible adverse effects of the FDA's Proposed Rule on Laboratory-Developed Tests for these clinical conditions and the broader spectrum of NTDs.